Compliance With the National SEP-1 Quality Measure and Association With Sepsis Outcomes: A Multicenter Retrospective Cohort Study*. Issue 10 (October 2018) - Rhee, Chanu; Filbin, Michael R.; Massaro, Anthony F.; Bulger, Amy L.; McEachern, Donna; Tobin, Kathleen A.; Kitch, Barrett T.; Thurlo-Walsh, Bert; Kadar, Aran; Koffman, Alexandra; Pande, Anupam; Hamad, Yasir; et al.
Abstract : Objectives: Many septic patients receive care that fails the Centers for Medicare and Medicaid Services' SEP-1 measure, but it is unclear whether this reflects meaningful lapses in care, differences in clinical characteristics, or excessive rigidity of the "all-or-nothing" measure. We compared outcomes in cases that passed versus failed SEP-1 during the first 2 years after the measure was implemented. Design: Retrospective cohort study. Setting: Seven U.S. hospitals. Patients: Adult patients included in SEP-1 reporting between October 2015 and September 2017. Interventions: None. Measurements and Main Results: Of 851 sepsis cases in the cohort, 281 (33%) passed SEP-1 and 570 (67%) failed. SEP-1 failures had higher rates of septic shock (20% vs 9%; p < 0.001), hospital-onset sepsis (11% vs 4%; p = 0.001), and vague presenting symptoms (46% vs 30%; p < 0.001). The most common reasons for failure were omission of 3- and 6-hour lactate measurements (228/570 failures, 40%). Only 86 of 570 failures (15.1%) had greater than 3-hour delays until broad-spectrum antibiotics. Cases that failed SEP-1 had higher in-hospital mortality rates (18.4% vs 11.0%; odds ratio, 1.82; 95% CI, 1.19–2.80; p = 0.006), but this association was no longer significant after adjusting for differences in clinical characteristics and severity of illness (adjusted odds ratio, 1.36; 95% CI, 0.85–2.18; p = 0.205). Delays of greater than 3 hours until antibiotics were significantly associated with death (adjusted odds ratio, 1.94; 95% CI, 1.04–3.62; p = 0.038), whereas failing SEP-1 for any other reason was not (adjusted odds ratio, 1.10; 95% CI, 0.70–1.72; p = 0.674). Conclusions: Crude mortality rates were higher in sepsis cases that failed versus passed SEP-1, but there was no difference after adjusting for clinical characteristics and severity of illness. Delays in antibiotic administration were associated with higher mortality but only accounted for a small fraction of SEP-1 failures. SEP-1 may not clearly differentiate between high- and low-quality care, and detailed risk adjustment is necessary to properly interpret associations between SEP-1 compliance and mortality. Abstract : Supplemental Digital Content is available in the text.